INVESTIGATING THE IMPACT OF ENGLISH CAMP ACTIVITIES; THE STUDENT STUDY SERVICE'S PERSPECTIVE - ., Nuraeni; Kamila, Hida (EDUKHA : Jurnal Penelitian dan Pengabdian kepada Masyarakat, 2020)
In order to enhance the students' outcomes in English learning, English camp is one of teaching activities that integrates various skills of teaching techniques and increases students' learning outcome. The purpose of this study was to determine the impact of English camp based on the perspective of the student study service. The methods consisted of collecting data from five students study service, selected by random sampling with interviews, and data analysis by study casus. The findings reveal positive and negative impact of english camp activities